2022
DOI: 10.1007/s40415-022-00820-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of seaweed extract on improvement drought tolerance of wheat revealed by osmoprotectants and DNA (cpDNA) markers

Abstract: Drought stress is one of the most severe abiotic stresses affecting adversely plant growth, crop production, and various metabolic processes. Using seaweed extract in mitigating water stress adverse effects is highly important for plant production. The present study discussed the physiological role of seaweed extract (Sargassum denticulatum) in improving wheat tolerance to water stress.Water stress (40% of field capacity) caused significant decreases in wheat plant growth parameters (shoot height, fresh, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…( Drobek et al, 2019). Our findings agreed with past research on wheat (Ali et al, 2022), Zea mays (Al-Shakankery et al, 2014), as well as Vigna sinensis (Sivasankari et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…( Drobek et al, 2019). Our findings agreed with past research on wheat (Ali et al, 2022), Zea mays (Al-Shakankery et al, 2014), as well as Vigna sinensis (Sivasankari et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, this memory increases the plant's tolerance when it is subsequently exposed to various abiotic stress (Giordano et al, 2020). Priming agents, such as seaweed extract and hormones or polyamines (PAs) have been shown to enhance wheat seedling performance (Afzal et al, 2006 andAli et al, 2022) and validamycin A in rice (Abdelgawad et al, 2014). Such memory works at the phenotypic level (Hilker et al, 2015) and considers changes in gene expression, metabolism, and epigenetic modifications but not DNA sequence changes.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed extract of Sargassum denticulatum (2 percent) foliar application enhanced all growth and yield parameters and more accumulation of the organic solutes in leaves of water-stressed plants. Application of seaweed biostimulant/extract enhanced seedling growth of wheat plants during growth period [38]. The influence of three red marine algae species (Laurencia obtusa, Corallina elongata, and Jania rubens) was assessed as biostimulant to enhance the growth of maize (Zea mays L.) plants.…”
Section: Common Seaweeds Species In Ocean (A) Rhodophyceae (Red Algae...mentioning
confidence: 99%
“…The reason for the high average values of chlorophyll for the plants treated with the physiological stimulant is due to the stimulant's content of seaweed extracts that contain the microelements zinc, manganese and gibberellin, which raised the efficiency of photosynthesis and thus raised The content of chlorophyll in the flag leaf.This is in agreement with [55], who indicated that seaweed extract applied as a foliar spray enhanced the level of leaf chlorophyll in plants by means of stimuli present in its composition. [56] . Extracts of marine algae improve chlorophyll concentration by phytohormones included in these extracts, which protect chlorophyll from degradation under heat stress and increase nitrogen assimilation.…”
Section: Chlorophyll Content In Leavesmentioning
confidence: 99%